In Situ Tumor Vaccine Expressing Anti-CD47 Antibody Enhances Antitumor Immunity - Zhang, Bin; Shu, Yongheng; Hu, Shichuan; Qi, Zhongbing; Chen, Yanwei; Ma, Jinhu; Wang, Yunmeng; Cheng, Ping (Frontiers in Oncology, 2022)
In situ tumor vaccine is a potential cancer therapy due to their advantages in induction of antitumor immune responses. Oncolytic virotherapy utilizes natural or engineered oncolytic viruses to kill tumors selectively, representing a promising in situ tumor vaccine for cancer immunotherapy. In addition to direct oncolysis, oncolytic viruses elicit potent and durable antitumor immune responses by induction of immunogenic cell death of tumors. Membrane protein CD47 overexpressed on tumor cells engages in "don't eat me" signal that prevents macrophages from engulfing tumor cells. CD47-targeting agents have been tested via preclinical and clinical trials. As potential tumor vaccine vectors, oncolytic viruses can be engineered to express anti-CD47 antibodies to induce potentiated tumor killing. Therefore, we developed an adenovirus-based tumor vaccine loaded with a CD47-targeting nanobody fused with the IgG2a Fc protein. B16-F10 melanoma, A20 lymphoma, and 4T1 breast cancer models in immunocompetent mice were established to evaluated in vivo antitumor efficacy of in situ tumor vaccination. The tumor vaccine armed with a nanobody against CD47 induced durable suppression of the tumor and long-term survival of tumor-bearing mice, and also elevated the number of tumor-infiltrating immune cells with an activated immunophenotype, suggesting that it could remodel the tumor immune microenvironment. Systemic antitumor effects and immune memory were also observed in immunocompetent mice following in situ vaccination with the anti-CD47 tumor vaccines; tumorigenesis was completely inhibited in these mice after tumor re-challenge. The recombinant anti-CD47 tumor vaccine has an effectual antitumor activity and may be a promising antitumor agent.